2020
DOI: 10.3390/foods9111620
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Antioxidant, Sensory Properties, and Emotions Induced for the Consumers of Nutraceutical Beverages Developed from Technological Functionalised Food Industry By-Products

Abstract: This study aims to develop nutraceutical beverages containing food processing by-products in their formulation, and determine the opinion of consumers. This is done by testing whether they know that the main ingredients of the product are by-products, performing an overall acceptability test of the developed beverages, and evaluating the emotions induced by the newly developed beverages for consumers. The main ingredients used for the preparation of added-value beverages were fermented milk permeate (containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 145 publications
0
10
0
Order By: Relevance
“…with the selected sourdough LAB. In another study [86], the main ingredients used for the preparation of added-value beverages were fermented milk permeate (containing galactooligosaccharides), extruded and fermented wheat bran (containing 8.79 log 10 CFU g −1 viable LAB strains showing antimicrobial properties), and different fruit/berry by-products (as a source of antioxidants). The functional properties of the beverages were proved by evaluating their antimicrobial and antioxidant properties, as well as the viable LAB count during storage.…”
Section: Application Of Sourdough Lab For Higher-value Food and Nutra...mentioning
confidence: 99%
“…with the selected sourdough LAB. In another study [86], the main ingredients used for the preparation of added-value beverages were fermented milk permeate (containing galactooligosaccharides), extruded and fermented wheat bran (containing 8.79 log 10 CFU g −1 viable LAB strains showing antimicrobial properties), and different fruit/berry by-products (as a source of antioxidants). The functional properties of the beverages were proved by evaluating their antimicrobial and antioxidant properties, as well as the viable LAB count during storage.…”
Section: Application Of Sourdough Lab For Higher-value Food and Nutra...mentioning
confidence: 99%
“…It has been found that compounds from spices, herbs, or tea can improve the quality parameters of LM; however, their extraction requires expensive technologies [ 28 , 29 , 30 ]. LAB are generally recognised as safe and offer plenty of advantages: (I) they can improve flavour and texture [ 19 , 31 ]; (II) due to their antimicrobial [ 32 , 33 ] and antifungal [ 33 , 34 ] metabolites, they can be used as biopreservatives to extend shelf lives [ 34 , 35 ]; (III) they have antioxidant properties [ 36 , 37 ]. It has also been published that lactobacilli strains have a broad range of applications, including meat processing [ 19 , 31 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of phenolic-rich by-products is a good example of agri-food waste utilization for grapes [ 10 ], pomegranates [ 11 ], bananas [ 12 ], olives [ 13 ], oranges [ 14 ], and apples [ 15 ], which are rich in flavonoids, procyanidins, catechins, hydroxycinnamates, and chalcones [ 16 ]. The pomace of chokeberry, blueberry [ 17 ], strawberry [ 18 ], blackberry [ 19 ], and currants [ 20 ] is a good source of phenolic antioxidants and dietary fibers that can be used as bioactive products and food additives [ 21 ]. In addition to phenolics, agro-industrial fruit waste is a source of polymeric compounds as polysaccharides and polyphenol–polysaccharide conjugates with antioxidant, immunomodulatory, antiobesity and other bioactivities [ 22 ].…”
Section: Introductionmentioning
confidence: 99%